Purification of wild type and recombinant xylanases and evaluation of their arabinoxylan hydrolysis ability - Tuyen, Do Thi; Thu Ngan, Nguyen; Mai Anh, Dao Thi; Thi Hong Nhung, Nguyen (Vietnam Journal of Biotechnology, 2021)
Arabinoxylan hydrolyzing enzymes are very rich and diversified groups, among these, endo-1,4-β-xylanase is the most important group which catalyzes the cleavage of xylan main skeleton to release arabinoxylan oligosaccharides such as D-xylose, xylobiose, L-arabinose, xylotetraose, xylopentose.  This group of enzyme was efficiently produced from natural microorganism including bacteria, yeast and fungi and recombinant strains. In this study, we have purified wild-type and recombinant xylanase to compare the difference in hydrolysis products of these two enzymes. Using sephadex G-100 and DEAE-sephadex column chromatography, we have purified xylanase from wild-type Aspergillus niger DSM1957 with molecular weight of 25 kDa, specific activity of 3240 IU/mL, the purity increases 1.68 folds compare to crude extract, and a recovery rate of 36%. The recombinant enzyme from Pichia pastoris GS115/pPXlnA was purified by ProbondTM affinity chromatography column, with a molecular weight of 36 kDa; the purity increased 3.2 folds than the crude extract, and with the recovery efficiency of 21.1%. The activity of commercial wild-type xylanase was better than that of our recombinant and wild-type enzymes. Our wild-type xylanase could hydrolyze arabinoxylan into L-arabinose in 50 mM CH3COONa pH 5.0. Our results showed that xylanases purified from different sources were stable and highly specific to xylan. Xylanase has potential application in the production of high quality biotechnological products.